EFFICACY OF SAND FILTRATION, Moringa oleifera SEED AND ALUM TREATMENT IN REDUCTION OF COLIFORMS AND TOTAL BACTERIA IN STABILIZATION POND EFFLUENT - Babatunde A, Awopetu; Ikechuwkwu, Moses; Odeyemi, Olu (International Journal of Tropical Medicine and Public Health, 2020)
International Journal of Tropical Medicine and Public Health,volume 1,Issue 1,P.6